2013
DOI: 10.2971/jeos.2013.13026
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nanoparticle size on thermal diffusivity of gold nano-fluid measured using thermal lens technique

Abstract: A dual beam mode-mismatched thermal lens method has been employed to investigate the dependence of thermal diffusivity of gold nanofluid on nanoparticles sizes. The samples were prepared at various sizes by utilizing the gamma radiation method. In the dual beam mode-mismatched thermal lens a diode laser (532 nm) was used as an excitation beam and a He-Ne laser with the beam output at 632.8 nm was used as a probe beam. Thermal diffusivity of gold nano-fluid increased with the increasing particle sizes ranging f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…This can be explained by the fact that, with an increase in particle size, there is an increase in the multiple scattering from the Ag nanoparticles which leads to a large effective interaction length whichin turn results in an enhancement in nonlinear absorption [12]. The nonlinear absorption and nonlinear refractive index values observed in this experiment are in the same order of magnitude with the reported values by Shahriari et al [17] [18] [19] and one order of magnitude lower than those reported by Faraji et al [20]. Figure 6 shows the traces of the waveforms for the pump beam (black trace) and the probe beam (red trace).…”
Section: Z-scan Measurementssupporting
confidence: 86%
“…This can be explained by the fact that, with an increase in particle size, there is an increase in the multiple scattering from the Ag nanoparticles which leads to a large effective interaction length whichin turn results in an enhancement in nonlinear absorption [12]. The nonlinear absorption and nonlinear refractive index values observed in this experiment are in the same order of magnitude with the reported values by Shahriari et al [17] [18] [19] and one order of magnitude lower than those reported by Faraji et al [20]. Figure 6 shows the traces of the waveforms for the pump beam (black trace) and the probe beam (red trace).…”
Section: Z-scan Measurementssupporting
confidence: 86%
“…PTS is actively involved in the nondestructive characterization of dispersed systems, although there are almost no nanodiamond studies . Thermal lensing as a relatively simple and reliable method is among the most used photothermal modalities toward this aim. Still, in carbon nanomaterials, many factors may affect the thermal parameters and, thus, the results of measurements. , Thus, it is relevant to develop a methodology for photothermal-lens measurements of heat-conducting properties of nanodiamond-based dispersed solutions and within the framework of their wider physicochemical diagnostics. Thus, the aim of this study was to use PTM and time-resolved photothermal modalities as complementary methods to estimate photothermal and heat-transfer properties of hydrosols of detonation nanodiamonds for various brands and comparison with other methods.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the numerous studies employing techniques that allow direct access to the thermal conductivity and heat capacity of nanofluids, there are only a small number of studies that employ experimental techniques to directly obtain the thermal diffusivity of nanofluids. Some available methods and techniques are laser flash [7], hot-wire [8,9], photoacoustic [10][11][12], photopyroelectric [13], thermalwave resonator cavity [14], and the thermal lens technique [15]. The last one is based on the optical properties of a medium with optical absorption and has been employed previously to obtain the thermal diffusivity of colloids of superparamagnetic nanoparticles [16].…”
Section: Introductionmentioning
confidence: 99%